Fiscal Dependence of Timor-Leste on the Oil and Gas Sector: Challenges of Economic Diversification - Ximenes, Elias; Pandin, Maria Yovia R; Kusmaningtyas, Amiartuti (Sean Institute, 2025)
This study analyzes the fiscal dependence of Timor-Leste on the oil and gas sector and the associated challenges in achieving economic diversification. Using a quantitative descriptive approach and time-series secondary data from 2010 to 2023, the findings reveal that oil and gas revenues constitute 85–90% of the state’s total income. This high dependency has led to a vulnerable fiscal structure and limited progress in diversifying the economic base. Regression results show that fiscal dependence negatively affects economic diversification, while infrastructure, GDP per capita, and human development have significant positive impacts. Timor-Leste also ranks lowest among comparable countries in export diversification and structural balance. The study recommends a strategic shift toward investment in non-oil sectors such as agriculture, tourism, and light manufacturing, supported by institutional reform and human capital development. These efforts are essential to reduce fiscal risks and build a more resilient and inclusive economy.